Long work hours of mothers and fathers are linked to increased risk for overweight and obesity among preschool children: longitudinal evidence from Germany - Jianghong Li; Till Kaiser; Matthias Pollmann-Schult; Lyndall Strazdins (Journal of Epidemiology and Community Health, 2019)
[Background:] Most existing studies on maternal employment and childhood overweight/obesity are from the USA. They are predominantly cross-sectional and show a consistent linear association between the two. Less is known about the joint impact of fathers' and mothers' work hours on childhood overweight and obesity. [Objectives:] To examine the impact of maternal and paternal work hours on overweight/obesity among children aged 1–60.167emyears in Germany using longitudinal data. [Methods:] Child body weight and height and their parents' work hours were collected for 2413 children at ages 0–1, ages 2–3 and ages 5–6. Overweight and obesity was defined using the body mass index percentiles based on the Cole LMS-Method. Random effects model was conducted, adjusting for demographic, socioeconomic and health characteristics of parents and children. [Results:] Compared with non-employment, when mothers worked 35 or more hours per week, the risk for child overweight and obesity increased among preschool children. When fathers worked 55 or more hours per week, this effect was strengthened and maternal part-time hours (24–34 per week) also became a risk for child overweight and obesity. The effect was mainly found in high-income families. [Conclusions:] Both mothers' and fathers' long work hours matter to young children's overweight status. Employment protection and work time regulation for both working parents during the first 6 years of the child's life should be considered in future policy.
Keywords: 330; mothers' work hours; fathers' work hours; child overweight and obesity; Germany; SOEP